I IMPLEMENTASI TEORI VYGOTSKY TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI - Susanti Etnawati (JURNAL PENDIDIKAN, 2021)
This paper aims to describe language development in early childhood based on Vygotsky's theory. This paper is the result of library research, using qualitative analysis techniques in a deductive way. The results of the study obtained that the development of children's language skills can develop well, greatly influenced by the surrounding environment and assistance from adults around the child. ZPD (zone of proximal development) and scaffolding really help children achieve their highest abilities so that children can do it themselves without the help of adults around them. Recommendations for teachers to act as facilitators for children in learning, help and support children when needed so that children can achieve maximum development of abilities from within themselves.